Submission by appearance, examination as to jurisdiction and compatibility among legal instruments in compensation claims for cancellation of the flight to passengers against air companies: comments on the court order C- 9/2022 of the Spanish Commercial Court sec. 9 of La Coruña - Ruiz Martín, Anna María (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
For certain subjects, there are several legal instruments which coexist together to deal with the same legal issues. This coexistence may lead to confusion for the legal operators which hesitate what is the proper instrument to be applied to the case. This situation usually occurs in air passengers’ transportation claims as the operators have, at least, several instruments to seize the jurisdiction and to claim for compensation. Nevertheless, the Court of Justice of the European Union (CJEU) has handled down a seminal case law on the subject, which interpret these relevant aspects relating to the compatibility among the general EU PIL instruments with special Conventions concerning the procedural problems that those have not regulated, such as the submission by appearance. This judicial resolution, subject to the analysis and decreed by a Spanish lower Court navigates on these problems.